Aspectos clínico-epidemiológicos, diagnóstico e controle da infecção por Trypanosoma vivax em rebanho bovino no estado do Maranhão - Pereira, Hélio Domingos (2017)
In the state of Maranhão, breeding cattle is important in the region's economy and is growing, but in properties in the municipality of Timon there are reports that some animals present clinical signs suggestive of trypanosomiasis. The objective of this study was to investigate the occurrence of trypanosomiasis in a dairy farm in this municipality Of Timon, state of Maranhão. The owner reported abortus, births of weak calves, and mortality of adult animals with progressive weight loss. Visits to the property were carried out to obtain the history, realize animal examination and blood collection for the Woo test, hemograms, serological tests for trypanosomiasis, leptospirosis, and neosporosis and PCR for molecular diagnosis of T. vivax. The identification of animals with low values in the hematocrit was the main hematological alteration identified in the herd. Two animals were positive in the Woo test, and trypanosomes were visualized in blood smears, confirmed by molecular diagnosis as T. vivax. It was identified that 95.23% (40/42) of the animals with low hematocrit were serologically positive for T. vivax. The conditions identified in the property as an environment propitious to mechanical vectors, the presence of wild animals and the introduction of animals from states where trypanosomiasis outbreaks had already been reported were probably associated with the introduction and dissemination of the agent in the herd. The occurrence of abortions without the manifestation of other clinical signs of trypanosomiasis suggests that these could also be associated with other diseases, such as leptospirosis, since high titers were identified in the animals tested. The high number of serologically positive animals for trypanosomiasis 82.51% (151/183) shows that almost all the herd had contact with the agent. The good nutritional status of the animals and the adoption in the herd of adequate sanitary measures probably ensured an efficient immune response at the time of initial contact of the animals with the agent, avoiding high rates of morbidity and mortality. The rapid establishment of control measures, including the use of trypanocidal drugs, contributed to the control of the outbreak. No more deaths and significant improvement was observed in the animals with symptoms of the disease. Despite the difficulty in accounting for the damages resulting from the diseases, it was observed that these were very expressive. The study allowed verifying the occurrence of the first outbreak of Trypanosoma vivax in the state of Maranhão, Brazil. The environmental condition identified in the property, associated with the intensification of animal husbandry practices, favored the occurrence of the trypanosomiasis and caused serious productive losses. The clinical diagnosis of the disease was difficult by the similarity of the clinical signs of trypanosomiasis with other diseases and the possibility of association of two or more diseases in the same patient, which emphasizes the importance of establishing adequate diagnostic measures as a way to avoid the dissemination of the disease and to minimize the economic losses of the producers.